Navigating emotional labour with emotional competence: insights from midwifery. (3rd July 2022) - Plimmer, Geoff; Franken, Esme; Franken, Margaret
ABSTRACT: Emotional competence is increasingly seen as essential across a wide range of jobs, and is often demanded of women in highly gendered and poorly rewarded jobs. Scholars have identified that emotion work extends beyond emotional labour to also include the triangle of power, in which emotion strategies are conducted between managers, workers and customers. We explored midwives' notions of emotional competence, including the strategies used, and the role of the client in determining such strategies – one of the poles in the service triangle: between managers, workers, and customers, where the burden of emotional work is negotiated through alliances and coercion. These aims were explored through qualitative data generated from an online questionnaire with 192 New Zealand midwives. Midwives showed awareness of their own emotional competence, and most saw this as both an aspect of professionalism, and an inherent attribute along with associated skills such as empathy. Emotional competence was relational and situational. While authenticity was highly valued and enacted through strategies such as establishing genuine connections with clients, surface acting was still necessary and took its toll. We advocate that midwives receive more recognition for the positive strategies they enact, and also more planned support from their organisations.